Comparison of floral fragrance components of species of Encyclia and Prosthechea (Orchidaceae) from Soconusco, southeast Mexico - Del Mazo Cancino, Alejandro; Damon, Anne (Lankesteriana: International Journal on Orchidology, 2006)
We analyzed the volatile fragrance components of flowers of four species of Prosthechea and three species of Encyclia, from the lower and middle altitudes of Soconusco region in the southeast of Mexico. The flowers of P. cochleata, reported to be an autogamic species, produced no volatiles. P. baculus, P. chacaoensis and P. radiata, all of which have highly fragrant flowers, shared various volatile components, most notably, p-methyl anisole, e-ocimene, oxophorone, a-farnesene and benzyl benzoate. E. adenocarpa has lightly fragrant flowers, with hexadecene and e-nerolidol the major components, whereas the physically similar E. parviflora produced mainly 3,4,5-trimethoxybenzoic acid, methyl ester and only one other compound. E. cordigera is a highly fragrant species and produced relatively large amounts of cis-geraniol. Various volatile fragrance components were shared by these two, recently separated genera, especially benzaldehyde, cis-ocimene and e-ocimene. Similarities were greater between the Prosthecheas (excluding P. cochleata) than the Encyclias.